KOMPETENSI APARAT DESA PADA PELAKSANAAN PROGRAM PEMBERDAYAAN MASYARAKAT DI DESA EFI – EFI KECAMATAN TOBELO SELATAN KABUPATEN HALMAHERA UTARA - WESARA, RISTO; TULUSAN, FEMMY; LALOMA, ALDEN (Sam Ratulangi University, 2019)
This study aims to determine competence in terms of aspects of knowledge, skills, and attitudesof the village officials Efi-Efi District of South Tobelo towards their work. This research method isqualitative descriptive and research focus in Efi-Efi Village, South Tobelo District, North HalmaheraRegency with data collection techniques conducted through interviews, observation and documentation.The research data obtained were processed using qualitative analysis, namely data reduction, datapresentation and conclusion drawing. The results showed that the competence of the village apparatus ofthe Efi-Efi District of South Tobelo District, North Halmahera Regency was still not good. This can beseen based on the results of the interview by looking at indicators of knowledge, skills and attitudes. Fromthe results of this study, it can be concluded that the Competency of the Efi-Efi Village Apparatus in theDistrict of South Tobelo, North Halmahera Regency is still not good enough. This needs to be consideredso that local governments can increase the competence of their village apparatus.Keywords: Competence of Village Apparatus